PEMBERDAYAAN “RUMAH TAHFIDZ” DALAM PEMBENTUKAN KARAKTER SANTRI (Studi Pemberdayaan Masyarakat di bidang Keagamaan di Kabupaten Tanah Datar ) - Irwandi Irwandi (Tazkir: Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2022)
Abstract Article 31 of the 1945 Constitution indicates the importance of education and regulation in the country which contains basic education which is interpreted as character education with personality growth. The character education in question essentially includes matters relating to religion, honesty, tolerance, discipline, hard work, creative, independent, democratic, curiosity, national spirit, love for the homeland, respect for achievement, friendly/communicative, peace-loving, fond of reading. , care for the environment, care about social, responsibility. In accordance with the demands of the 1945 Constitution, the local government together with the community realize a form of character education with the establishment of the "Tahfidz house" which aims to give birth to hafidz/zah in Kab. Flat Land. And basically it also teaches the values of character education. The results of the establishment of “rumah tahfidz” will be examined using a qualitative method with a descriptive approach. With the findings that the "Tahfidz house" in Tanah Datar Regency has shown results both quantitatively and qualitatively, in various forms including increased religious attitudes, honesty, tolerance, discipline, hard work, respect for achievement, friendly/communicative, and responsibility.Keywords: "Tahfidz House, Character, Empowerment" Abstrak Pasal 31 Undang-undang Dasar 1945 menisyaratkan tentang arti pentingnya pendidikan dan pengaturan di tanah air yang memuat tentang pendidikan dasar yang dimaknai dengan pendidikan karakter dengan pertumbuhan kepribadian. Pendidikan karakter dimaksud pada hakekatnya memuat hal yang berkaitan dengan religius, jujur, toleransi, disiplin, kerja keras, kreatif, mandiri, demokratis, rasa ingin tahu, semangat kebangsaan, cinta tanah air, menghargai prestasi, bersahabat/komunikatif, cinta damai, gemar membaca, peduli lingkungan, peduli sosial, tanggung jawab. Sesuai tuntutan UUD 1945 maka pemerintah daerah bersama masyarakat mewujudkan bentuk pendidikan karakter dengan berdirinya “rumah tahfidz”yang bertujuan untuk melahirkan para hafidz/zah di Kab. Tanah Datar. Dan pada dasarnya juga mengajarkan nilia-nilai pendidikan karakter.. Hasil dari berdirinya “rumah tahfidz”  ini akan di teliti dengan menggunakan metode Kualitatif dengan pendekatan Deskriptif. Dengan temuan bahwasanya “rumah tahfidz” di Kabupaten Tanah Datar telah memperlihatkan hasil baik secara kuantitatif maupun kualitatif, dengan berbagai bentuk yang diantaranya peningkatan sikap religius, jujur, toleransi, disiplin, kerja keras, menghargai prestasi, bersahabat/komunikatif, dan  tanggung jawabKata Kunci: “Rumah Tahfidz, Karakter, pemberdayaan